ChemInform Abstract: Synthesis, Stereochemistry, Structural Classification, and Chemical Reactivity of Natural Pterocarpans. Issue 18 (11th April 2013) - Goel, Atul; Kumar, Amit; Raghuvanshi, Ashutosh
Abstract Review: 268 refs.